Levantamento histórico, sócio-cultural e paisagístico do largo das mercês em Tiradentes, Minas Gerais - Gomes, Arthur Moraes (2021)
The population nucleus that would give rise to the current city of Tiradentes-MG emerged in 1702 from the discovery of gold in the Rio das Mortes region by explorers who crossed the roads of the Estrada Real. During the urbanization process, squares and squares were built and, today, because they are part of history, they are considered part of the city's heritage. Called Historic Gardens and, common in colonial cities in Minas Gerais, these landscaped spaces strengthen the population's memory and identity and also contribute to an increase in the quality of life. Considering the importance of historic gardens, this research aimed to study the historical, socio-cultural and landscape evolution of Largo das Mercês, in order to verify the morphological transformations and representations of space for the city of Tiradentes. To carry out the research, a subjective analysis was carried out in conjunction with an inventive analysis, using techniques for the conservation and preservation of historic gardens. Thus, a documental survey was carried out together with a bibliographical and iconographic research. In addition, field research was carried out, where interviews were carried out with people linked to research on the material and immaterial heritage of Tiradentes. The plant species found throughout the history of the square were identified based on reports, documents and iconographies. Combining the data made it possible to trace the historical process and identify the transformations in the space of Largo das Mercês. Due to the presence of the Church of Nossa Senhora das Mercês and for being close to the city's exit, the square was used for religious practices and mainly as a place of passage until the 19th century. In a slow process of occupation, it turned into a large urban green area in the center of Tiradentes and since its origin it has been used for different social practices. Conceived by Roberto Burle Marx, the first landscaping project at Largo das Mercês was implemented at the end of the 20th century. Since its origin, it has remained in its classic form, a large lawn with arboreal species composing the landscape and with few changes in space over time. The square has a unique style, and is currently one of the main tourist attractions in Tiradentes.